Ground water as the source of an outbreak of Salmonella Enteritidis - Ana Kovačić; Željko Huljev; Edita Sušić (Springer, 2019)
In September 2014, an outbreak of gastroenteritis was reported to the Public Health Institute of Šibenik and Knin County in Croatia. The outbreak occurred in the County center of Šibenik, a town with 50,000 inhabitants, and it lasted for 12 days. An epidemiological investigation suggested a nearby water spring as the source of the outbreak. Due to the temporary closure of the public water supply system, the inhabitants started to use untreated water from a nearby spring. Microbiological analysis revealed that the outbreak was caused by Salmonella enterica subsp. enterica serovar Enteritidis that was isolated from stool samples of the patients and ground water. The isolates were further analysed with pulsed-field gel electrophoresis using XbaI, which revealed an identical macrorestriction profile. Although 68 cases were reported, it was estimated that the actual number of affected persons was more than several hundred. In order to prevent further spread of disease, public advice was released immediately after the first epidemiological indication and a warning sign was placed at the incriminated water source, after microbiological confirmation. It is necessary to regularly monitor microbiological quality of ground water especially in urban areas and provide adequate education and awareness to the inhabitants regarding the risk of using untreated ground water.